The noonday friends - Stolz, Mary, 1920-2006.; Glanzman, Louis S., 1922-2013 (New York : Scholastic Inc., 1965)
Franny dreams of becoming a ballerina. She doesn't share her dreams with too many friends because she must babysit her brother while her mother works.
Keywords: Friendship -- Fiction